2014
DOI: 10.1063/1.4901085
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of mixtures of a polymer and a cholesteric liquid crystal under an external field

Abstract: We present a mean field theory to describe phase behaviors in mixtures of a polymer and a cholesteric liquid crystal under an external magnetic or electric field. Taking into account a chiral coupling between a polymer and a liquid crystal under the external field, we examine twist-untwist phase transitions and phase separations in the mixtures. It is found that a cholesteric-nematic phase transition can be induced by not only the external field but also concentration and temperature. Depending on the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The effect of magnetic fields on the temperature at which the cholesteric crystalline state to isotropic state transition occurs is important because these devices are to be used at varying magnetic fields (0.5 T to 7 T). Previous studies on LCs show negligible effects (less than 0.1°C) on the transition temperature for a small sampling of LC molecules …”
Section: Theorymentioning
confidence: 84%
“…The effect of magnetic fields on the temperature at which the cholesteric crystalline state to isotropic state transition occurs is important because these devices are to be used at varying magnetic fields (0.5 T to 7 T). Previous studies on LCs show negligible effects (less than 0.1°C) on the transition temperature for a small sampling of LC molecules …”
Section: Theorymentioning
confidence: 84%
“…The ϵ does not depend on z and remains constant. Based on the Matsuyama theories [21,23,24] of a N TB phase and molecular field theory for the N* phase of Liu-Liu and coworkers [37,38], we introduce the expression for the N TB phase by including the third-order Legendre polynomial term in the chiral part of interaction potential in addition to second-order Legendre polynomial term. Let N L be the number of LC molecules of length L and diameter D.…”
Section: Free Energy Relation For a Twist-bend Nematic Phasementioning
confidence: 99%
“…In an interesting work, Matsuyama [21] introduced a meanfield theory to describe N TB phase. Based on the previous works [23,24] of the N* phase, the coupling between nematic director and pitch axis of N TB phase has been incorporated. Barbero et al [36] developed an elastic theory for the description of N TB phase by taking into account such a coupling term.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature and concentration dependence of the CLC helical pitch has been widely reported. 7 Recently Matsuyama 49,50 showed that the helical pitch of a cholesteric phase is a function of the concentration and the orientation order parameter in a mixture of polymer and a liquid crystal. In the present study, we assume that the helix pitch changes in response to humidity level from the swelling and shrinking of the polysaccharide matrix through water sorption.…”
Section: A Geometry and Structurementioning
confidence: 99%